Integrasi Teknik Invigorasi Benih dengan Rizobakteri untuk Pengendalian Penyakit dan Peningkatan Hasil Tomat - Gusti Ayu Kade Sutariati; Abdul Madiki; Andi Khaeruni (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
The effects of pre-planted seed invigoration treatment integrated with rhizobacteria were studied in an attempt to control fusarium wilt disease and to improve yield of tomato in the field. Seed treatments consisted of seed invigoration with single or mixture rhizobacteria, burned rice husk or sawdust seed matriconditioning, integrated seed matriconditioning with single or mixture rhizobacteria, seed hydration, and fungicide seed treatment. The result showed that the most effective treatment was the integration of rice hull charcoal seed matriconditioning with Bacillus polymixa BG25. The seed treatment increased total fruit and fruit weight by 40% and 166% , respectively. The treatment was also effective in suppressing disease incidence by 70%. Based on this experiment, rhizobacteria B. polymixa BG25 integrated with rice hull charcoal seed matriconditioning can be recommended as biocontrol agents in improving yield and controlling fusarium wilt disease of tomato.